Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Konsumen Daging Ayam Broiler Di Kecamatan Tambun Selatan Kabupaten Bekasi - Ilyas Syaiful Haq; Muharam Muharam; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
The average meat requirement in Indonesia is met from boiler chicken meat. South Tambun sub-district has the largest population in Bekasi Regency and Bekasi Regency is the area with the highest per capita income and district minimum wage in Indonesia. Even so, the consumption of broiler meat in Tambun Selatan District, Bekasi Regency, West Java can be said to be low so that it does not meet nutritional needs. This study aims to: (1) analyze the factors that influence the demand for broiler chicken simultaneously; (2) Analyzing the factors that affect the demand for Broiler Chicken Partially. The data used in this study is primary data through the distribution of questionnaires using google form by household consumers (Cross-section). Respondents in this study were 100 respondents obtained using the Slovin formula. Data analysis used multiple linear regression formula assisted by Microsoft Excel and EViews 10 applications. The results showed that 37,8% of consumer demand for broiler chicken could be explained by the independent variables used in the multiple linear regression equation model. All independent variables have a significant effect on the demand for broiler meat. The number of family members, the number of family incomes, and the level of education simultaneously have a significant effect on the demand for broiler meat.